EU terrorism situation and trend report TE-SAT / EUROPOL / 2015 (EU terrorism situation and trend report TE-SAT, 2015)
This report presents the situation with regard to terrorism and violent extremism as it unfolded in 2014. It does not make predictions on how terrorism and violent extremism will develop. However, based on historical data and expert judgments, the report identifies a number of trends that will help in defining the threat these phenomena pose to the EU. It will hopefully be of use in concerted efforts to reduce both opportunities for, and the impact of, future terrorist attacks, as well in preparing effective action should such incidents take place.